The role of culture in early childhood curriculum development: A case study of curriculum innovations in Hong Kong kindergartens. (March 2022) - Yang, Weipeng; Li, Hui
This study employed an inductive qualitative approach to understanding the effects of local culture on early childhood curriculum development in two Hong Kong kindergartens. A triangulation of interviews, observations and documents was established, and cultural-historical activity theory was employed as the theoretical framework. The results indicated that local culture played an important role in early childhood curriculum development. First, the two cases learned from diverse models and approaches during the transformation of their curricula, resulting in contradictory demands and motives. Then, these contradictions were, in turn, resolved by the local culture to achieve curriculum hybridisation and innovation, as well as inherit the culture. Such findings provide valuable implications for early childhood professionals to integrate social and cultural diversity into curriculum development and to localise imported curricular practices so as to ensure a good fit between the curriculum and the local context.